Implications Juridical Council Regulation Honorary Center Notary Association of Indonesia Number 1 of 2017 About The Limits of Fairness Total Creation Agreement in Semarang - Adwin Adwin; Yanto Irianto; Munsharif Abdul Chalim (Jurnal Akta, 2018)
The purpose of writing  article is to know and the Honorary Board of Indonesian Notary Association Center for the Determination of Regulation No. 1 of 2017 on the Fairness Limit Per day Total Creation Agreement. This research methods to achieve the objectives of  law is the law of sociological or empirical research. Results of the research which set the contents of  regulation on the restriction of the notary in the agreement a day in which a number of 20 (twenty) in a day. Destinations create those rules for protecting Notary and society who use the services of a Notary, in  case the Honorary Board of Indonesian Notary Association has authority in making these regulations mandate based on the Notary Act. Sanctions For notaries who violate these rules can be wearing the Internal sanctions in question is the organizational and External sanctions.Keywords: Honorary Council Regulation, The Authority, Sanctions.